(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Relevance of the work is to study the effect of quercetin and lipoate in the treatment of experimental diabetes. Purpose. Explore the possibility of correcting violations of glycolytic processes in the retina using quercetin and lipoate with streptozotocin diabetes. Methods. Studies were conducted on 55 white rats. Experimental animals were divided into four groups: first — control group (14 rats), the second — experimental group (14 rats), animals with diabetes, without the use of drugs, the third — the experimental group (12 rats), animals with diabetes, and the use of lipoic acid, Results. In the context of the application of lipoic acid and quercetin metabolites showed a decrease carbohydrate-phosphorus metabolism in the retina and the blood of experimental animals with streptozotocin diabetes. Conclusion. 1. The test drug prevents the degree of violation redox processes in the retina. This was confirmed by a decrease in lactate and pyruvate concentrations in the retina in diabetic animals in the study drugs application (bioflavonoid — quercetin and thiol preparation — lipoate). 2. The most pronounced protective effect on the degree of violation of anaerobic and aerobic glucose oxidation in retina characteristic of lipoic acid. 3. Study drug (bioflavonoid — quercetin and thiol compound — lipoic acid) showed its positive metabolic effect and at the system level. Thus, after 6 months of the experiment under the influence of lipoic acid lactate levels decreased by 37.6 % and pyruvate — 26.2 %, and the quercetin when exposed to lactate was reduced by 35.3 % and pyruvate — 22, 7 % compared to diabetic animals without drug experimentthe fourth — the experimental group (15 rats), animals with diabetes and the use of quercetin. In retinas homogenates and plasma produced determination of pyruvate and lactate.